2014
DOI: 10.1186/1297-9716-45-53
|View full text |Cite
|
Sign up to set email alerts
|

Infected or not: are PCR-positive oropharyngeal swabs indicative of low pathogenic influenza A virus infection in the respiratory tract of Mallard Anas platyrhynchos?

Abstract: Detection of influenza virus in oropharyngeal swabs collected during wild bird surveillance is assumed to represent respiratory infection, although intestine is the main site of infection. We tested this assumption by histological examination of the respiratory tract of wild Mallards with virus-positive oropharyngeal swabs. Thirty-two of 125 Mallards tested had viral-RNA positive oropharyngeal swabs. The respiratory tracts of four Mallards with the most virus were examined in detail by immunohistochemistry. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…A similar observation has been described previously in chickens [23]. One potential explanation for the one quail that only shed on 7 DPI is that the apparent shedding observed in this animal was simply associated with the ingestion of virusladen water [20], as viral RNA was detected on several DPI in the water bowls of both quail cages (Table 2). However, this explanation appears unlikely for the second quail that failed to seroconvert, as this bird shed during 6-9 DPI, and shed in greater quantities than its cage-mate, which was the only other quail shedding on 6 DPI ( Table 1).…”
Section: Discussionsupporting
confidence: 86%
“…A similar observation has been described previously in chickens [23]. One potential explanation for the one quail that only shed on 7 DPI is that the apparent shedding observed in this animal was simply associated with the ingestion of virusladen water [20], as viral RNA was detected on several DPI in the water bowls of both quail cages (Table 2). However, this explanation appears unlikely for the second quail that failed to seroconvert, as this bird shed during 6-9 DPI, and shed in greater quantities than its cage-mate, which was the only other quail shedding on 6 DPI ( Table 1).…”
Section: Discussionsupporting
confidence: 86%
“…Fecal samples, on average, contained a larger amount of viral RNA than cloacal swabs, possibly as a consequence of the fact that fecal samples contained more material from the beginning. A question that still needs attention is whether positive detection in oropharyngeal samples proves actual replication, as a recent study in mallards found no evidence for replication of LPAI virus in the oropharyngeal tract even if there was a positive detection by molecular techniques in the birds (31). Nevertheless, different hosts (i.e., taxonomic groups) may vary in predominant replication sites based on differential expression of viral receptors, and at the same time, different virus strains can vary in tissue tropism, like the HPAI H5N1virus, which replicates primarily in the respiratory tract (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…We performed one‐step rRT‐PCR to screen for influenza A virus by targeting the matrix (M) gene, and all influenza A‐positive samples were further subjected to rRT‐PCR for H5 subtyping using H5a‐ and H5b‐specific primers and probes as previously described . A sample was considered positive for detection of influenza A virus RNA if the cycle of threshold ( C t ) was lower than 40 . We did not attempt to test for H9, H7, or other subtypes of influenza as our focus was on the H5 subtype which has occurred commonly in Bangladesh.…”
Section: Methodsmentioning
confidence: 99%
“…31 A sample was considered positive for detection of influenza A virus RNA if the cycle of threshold (C t ) was lower than 40. 32 We did not attempt to test for H9, H7, or other subtypes of influenza as our focus was on the H5 subtype which has occurred commonly in Bangladesh.…”
Section: H5 Antibody Detection By Competitive Enzyme-linked Immunosmentioning
confidence: 99%
See 1 more Smart Citation